The Relationship of Mindfulness, Self-Differentiation and Alexithymia With Borderline Personality Traits - Masoud Bagheri; Akram Khodai (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Psychological problems such as borderline personality traits can negatively affect students' behaviors, cognition, interpersonal communication and academic achievement. It is important to identify factors such as mindfulness, self-differentiation, and alexithymia and determine their relationship these traits. Objectives: This study was performed to investigate the relationship of mindfulness, self-differentiation and alexithymia with borderline personality traits. Methods: In this descriptive correlational study, 309 students from Shahid Bahonar University of Kerman (217 female and 92 male) were selected using the random cluster sampling method. They completed the Five Factor Mindfulness Questionnaire, the Self-Differentiation Scale, the Toronto Alexithymia Scale and the Borderline Personality Scale. After collecting the questionnaires, the data were analyzed using SPSS-24 and AMOS-24 software programs and path analysis method. Results: The analyses showed that the direct effect of mindfulness was significant only on fear of intimacy (p <0.05). Self-differentiation predicted three sub-scales of borderline personality including defense mechanisms, fear of intimacy (p <0.001) and reality testing (p <0.05) in a significant and negative manner. Alexithymia had a significant positive impact on all subscales of borderline personality including identity disturbance, primary defense mechanisms, fear of intimacy (p <0.001) and damaged reality testing (p <0.05). Conclusion: Alexithymia, self-differentiation and mindfulness were the most powerful predictors of students' borderline personality traits, respectively.